Imposing fees for police services in Australia. Issue 2 (3rd April 2021) - Dellora, Carlo; Beck, Luke
ABSTRACT: This article presents the first comprehensive overview and analysis of the Australian law and practice of imposing fees for unrequested police services. It acts on Lippert and Walby's recent call for scholarly analysis of user-pays policing 'to break free of standard disciplinary confines'. One aim of this paper therefore is to start filling this gap in the literature by giving more prominence to substantive legal analyses of user-pays policing. The purpose of this article is both practical and analytical. The practical purpose of this article is to contribute to the literature by providing a detailed examination of the legal framework for imposing fees for unrequested police services in Australia. The analytical purpose of this article is two-fold: to isolate imposing fees for police services as a distinct category of user-pays policing and to critically evaluate the practice of imposing fees for police services in one Australian jurisdiction as a case study.